2018
DOI: 10.1080/10255842.2018.1447104
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of corneal biomechanical and optical behavior to material parameters using design of experiments method

Abstract: The optical performance of the human cornea under intraocular pressure (IOP) is the result of complex material properties and their interactions. The measurement of the numerous material parameters that define this material behavior may be key in the refinement of patient-specific models. The goal of this study was to investigate the relative contribution of these parameters to the biomechanical and optical responses of human cornea predicted by a widely accepted anisotropic hyperelastic finite element model, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Second, we did not consider the contribution of the interaction effects between important biomechanical parameters (geometry, matrix stiffness, and fibril dispersion) on the IOP-induced changes in corneal wavefront aberrations. Our previous sensitivity study 19 showed that the interaction between the matrix stiffness and fibril dispersion had an impact on the IOP-induced changes in corneal optical aberrations, but the effects of interactions among geometry, matrix stiffness, and fibril dispersion have not yet been clearly quantified. Neglecting these interaction effects may also affect estimation of collagen fibril dispersion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Second, we did not consider the contribution of the interaction effects between important biomechanical parameters (geometry, matrix stiffness, and fibril dispersion) on the IOP-induced changes in corneal wavefront aberrations. Our previous sensitivity study 19 showed that the interaction between the matrix stiffness and fibril dispersion had an impact on the IOP-induced changes in corneal optical aberrations, but the effects of interactions among geometry, matrix stiffness, and fibril dispersion have not yet been clearly quantified. Neglecting these interaction effects may also affect estimation of collagen fibril dispersion.…”
Section: Discussionmentioning
confidence: 99%
“…The 3D anisotropic hyperelastic corneal models in this study were all developed using FE software (Abaqus Unified FEA; Dassault Systèmes Simulia Corp., Johnston, RI, USA) as described in our previous study 19 and shown in Figure 1 . An improved strain energy function from the original Gasser–Holzapfel–Ogden model 34 with pre-integrated fibril distribution was adopted to describe the microstructure of the cornea.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our analysis also found that the material parameters of the corneal and scleral tissues played an important role in their biomechanical and optical behavior. 28 The material parameters of the cornea significantly affect the displacement of the anterior and posterior corneal surfaces. Moreover, once the scleral elasticity maintained a constant, with the increase of corneal elasticity, the maximum stress and maximum displacement moved toward the edge of the cornea.…”
Section: Other Thoughtsmentioning
confidence: 99%